An Adjacent Atomic Platinum Site Enables Single‐Atom Iron with High Oxygen Reduction Reaction Performance. (21st July 2021) - Han, Ali; Wang, Xijun; Tang, Kun; Zhang, Zedong; Ye, Chenliang; Kong, Kejian; Hu, Haibo; Zheng, Lirong; Jiang, Peng; Zhao, Changxin; Zhang, Qiang; Wang, Dingsheng; et al.
Abstract: The modulation effect has been widely investigated to tune the electronic state of single‐atomic M‐N‐C catalysts to enhance the activity of oxygen reduction reaction (ORR). However, the in‐depth study of modulation effect is rarely reported for the isolated dual‐atomic metal sites. Now, the catalytic activities of Fe‐N4 moiety can be enhanced by the adjacent Pt‐N4 moiety through the modulation effect, in which the Pt‐N4 acts as the modulator to tune the 3d electronic orbitals of Fe‐N4 active site and optimize ORR activity. Inspired by this principle, we design and synthesize the electrocatalyst that comprises isolated Fe‐N4 /Pt‐N4 moieties dispersed in the nitrogen‐doped carbon matrix (Fe‐N4 /Pt‐N4 @NC) and exhibits a half‐wave potential of 0.93 V vs. RHE and negligible activity degradation (ΔE1/2 =8 mV) after 10000 cycles in 0.1 M KOH. We also demonstrate that the modulation effect is not effective for optimizing the ORR performances of Co‐N4 /Pt‐N4 and Mn‐N4 /Pt‐N4 systems. Abstract : We have designed an efficient oxygen reduction reaction (ORR) electrocatalyst of Fe‐N4 /Pt‐N4 @NC with Fe‐N4 and Pt‐N4 dual atomic sites. The enhancement for the ORR activity is demonstrated by the modulation effect: Pt‐N4 plays the role in modulating the Fe‐N4 active center to optimize the ORR performance. The modulation effect is not effective for the enhancement of ORR performance in the systems of Co‐N4 /Pt‐N4 @NC and Mn‐N4 /Pt‐N4 @NC.